The evaluation of parallel plate antenna with variation of air gaps separation and copper plate area - Mohammad S.A.; Ahmad M.R.; Alkahtani A.A.; Esa M.R.M.; Sidik M.A.B.; Nawawi Z.; Jambak M.I.; Baharin S.A.S.; Sabri M.H.M.; Yusop N.; Aziz M.Z.A.A.; Al-Khaleefa A.S.; et al. (Mattingley Publishing, 2023)
Lightning; Air-gaps; Computer simulation technology (CST); Cross correlation methods; Frequency components; Lightning detection; Lightning flashes; Parallel plates; Waveform amplitudes; Antennas